2004
DOI: 10.1248/bpb.27.1883
|View full text |Cite
|
Sign up to set email alerts
|

Anti-complementary Activity of Triterpenoides from Fruits of Zizyphus jujuba

Abstract: In order to determine on the anti-complement activity of triterpenes, following eleven triterpenoides were isolated from the fruits of the Zizyphus jujuba MILL: ceanothane-type triterpenes: colubrinic acid (1), zizyberenalic acid (11); lupane-type triterpenes: alphitolic acid (2), 3-O-cis-p-coumaroyl alphitolic acid (3), 3-O-trans-pcoumaroyl alphitolic acid (4), betulinic acid (7), betulonic acid (9); and oleanane-type triterpenes: 3-O-cis-pcoumaroyl maslinic acid (5), 3-O-trans-p-coumaroyl maslinic acid (6), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 26 publications
3
57
0
1
Order By: Relevance
“…There were identified as 3 -trans-p-coumaroyloxy-2R-hydroxyolean-12-en-28-oic acid and 3 -cis-p-coumaroyloxy-2R-hydroxyolean-12-en-28-oic acid according to the reported literature (30,31). The molecular formula of compound 11 was inferred as C 30 H 48 O 4 on the basis of analyses of ESI-MS and 1 H and 13 C NMR spectra, suggesting it had seven unsaturated degrees in the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…There were identified as 3 -trans-p-coumaroyloxy-2R-hydroxyolean-12-en-28-oic acid and 3 -cis-p-coumaroyloxy-2R-hydroxyolean-12-en-28-oic acid according to the reported literature (30,31). The molecular formula of compound 11 was inferred as C 30 H 48 O 4 on the basis of analyses of ESI-MS and 1 H and 13 C NMR spectra, suggesting it had seven unsaturated degrees in the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…From our study it may be concluded that the low dose of MEZJ (250 mg/kg) possess good hepatoprotective activity in chronic hepatitis induced by CCl 4 whereas low and medium dose of the MEZJ (250 mg/kg and 500 mg/kg) potentially ameliorates acute hepatitis induced by CCl 4 . The protective effect may be because of the presence of flavonoids and saponins in MEZJ.…”
Section: Discussionmentioning
confidence: 65%
“…The result indicated that MEZJ was effective in low and medium doses (250 and 500 mg/kg, p.o) at times of acute stress, whereas, during chronic damage to hepatocyte, only low dose (250 mg/kg, p.o) of MEZJ is potent enough to reverse the damaging effect of hepatotoxin such as CCl 4 . On the contrary, high dose (1000 mg/kg, p.o) of MEZJ was found to be least effective in presence of damage to liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…jujube showed significant protection against CCl4 intoxicated HepG2 cell lines by means of increased cell viability and decreased LDH levels compared to control group. It was reported for anticancer, anxiolytic, anti-complementary and hypoglycemic activities [23][24][25][26]. Jujuba methanol extraction with different concentrations inhibited the lipid peroxidation and significantly restored the liver function markers (Ast, Alt, Alp, LDH) IN Acute liver damaged) [27].…”
Section: Magic Fruit (Ziziphus Jujube)mentioning
confidence: 99%